Матрица рассеяния для волнового уравнения с финитным радиальным потенциалом в двумерном пространстве - Мильман, А.Л. (Український математичний журнал, 1993)
The expressions for partial scattering matrices Sl(λ) are obtained for any natural l by vising V. M. Adamyan's result which establishes the universal relationship between the scattering matrix for a wave equation with finite potential in an even-dimensional space and a characteristic operator function of a special contraction operator which describes the energy dissipation from the domain of the space which contains a dissipator. It is shown that the problem can be reduced to the case of l=0 for all even l and to the case of l=1 for all odd l.